Social Relations Behind Fraudulent Behavior: Enrichment of The Fraud Triangle Theory - Khairul Shaleh; Gugus Irianto; Ali Djamhuri; Noval Adib (Integrated Journal of Business and Economics (IJBE), 2021)
This research aims to understand how village budget fraud is likely to occur because of patron-client social relations in the village government bureaucracy. This research uses qualitative methodology with an ethnographic exploration approach. They were collecting data through field observations and in-depth interviews with informants. The selection of informants uses a snowball technique approach. The field findings show that the social relations of village government heads with political sponsors have decreased the accountability performance of the village government. Political sponsors are not part of the village apparatus but intervene in many bureaucratic affairs of the village government. That successfully created a patronage influence on the ranks of village devices. Such circumstances make the internal control system malfunction so that financial procedures do not run as they should. In the end, the bond of social relations in the bureaucratic environment gives rise to the tendency of fraud to the village budget. This research enriches the theory of triangle fraud by including elements of social relations in the model.